Continuation and effectiveness of tadalafil once daily during a 6‐month observational study in erectile dysfunction: the EDATE study. Issue 9 (14th August 2014) - Buvat, J.; Hatzichristou, D.; Boess, F. G.; Büttner, H.; Gehchan, N.; Henneges, C.; Porst, H.
Summary Aims This was the first observational study evaluating treatment continuation, effectiveness and tolerability of tadalafil 5 mg once daily (TAD‐OaD) in patients who chose and paid for treatment of erectile dysfunction (ED) in routine clinical practice. Methods Men ≥ 18 years with ED, treated previously with phosphodiesterase type 5 (PDE5)‐inhibitor on‐demand (PRN) or treatment‐naïve, were enrolled at 59 sites. For patients prescribed TAD‐OaD at baseline (T1), change in erectile function (IIEF‐EF and GAQ) was documented after 1–3 (T2) and 4–6 (T3) months. The primary outcome was the probability to switch/discontinue from TAD‐OaD, estimated by Kaplan–Meier (KM) product‐limit method. Changes in IIEF‐EF were evaluated using a mixed model for repeated measures adjusting for patient baseline characteristics. Results Of 975 men enrolled (median age 56.8 years, 33.7% with previous PDE5‐inhibitor use), 778 were prescribed TAD‐OaD, 135 TAD‐PRN and 62 sildenafil or vardenafil PRN. During the 6‐month longitudinal observation, 107 patients (13.8% of 778) switched or discontinued TAD‐OaD‐treatment. KM‐rates (95%CI) for continuing TAD‐OaD at 2, 4 and 6 months were 94.0% (92.3, 95.7), 88.3% (85.9, 90.6) and 86.3% (83.7, 88.9), respectively. The 25th percentile of time to switch/discontinuation of TAD‐OaD was estimated as 31.1 weeks (lower 95%CI 30.3 weeks). At T3, IIEF‐EF scores had increased by 7.1 (LSmean; 95%CI 5.8, 8.5) points; 91.3% of patients reported improved erections. The most frequently reported AE was headache (10 patients; 1.3%); no new/unexpected safety signals were observed. Conclusion Under routine conditions, and when patients were involved in treatment decision‐making, more than 86% of men starting/switching to tadalafil once daily (OaD) at baseline continued tadalafil OaD treatment for ≥ 6 months.